2019
DOI: 10.1101/686691
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Old Meets New: Combining Herbarium Databases with Genetic Methods to Evaluate the Invasion Status of Baby’s Breath (Gypsophila paniculata) in North America

Abstract: 28Aim: This paper aims to inform our knowledge of common baby's breath's (Gypsophila 29 paniculata) current population structure and invasion status using a combination of 30 contemporary genetic methods and historical herbarium data. 31 Taxon: Gypsophila paniculata (Angiosperms: Eudicot, Caryophyllaceae) 32 Location: Samples were collected from seven locations spanning a portion of the plant's North 33 American range: Washington, North Dakota, Minnesota, and Michigan, United States. 34 Methods: To analyze con… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 33 publications
2
13
0
Order By: Relevance
“…To better understand these mechanisms, we investigated two populations of G. paniculata growing at opposite ends of the species’ introduced range in the United States. Based on herbarium records, G. paniculata populations have been established in the sand dunes of Petoskey, MI, since the early 1910s and in the sagebrush steppes of Washington since the 1930s (Lamar & Partridge, 2019). This has likely provided sufficient time for these populations to begin adapting to these divergent ecosystems.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand these mechanisms, we investigated two populations of G. paniculata growing at opposite ends of the species’ introduced range in the United States. Based on herbarium records, G. paniculata populations have been established in the sand dunes of Petoskey, MI, since the early 1910s and in the sagebrush steppes of Washington since the 1930s (Lamar & Partridge, 2019). This has likely provided sufficient time for these populations to begin adapting to these divergent ecosystems.…”
Section: Discussionmentioning
confidence: 99%
“…We predict that the populations will differ in gene expression patterns and that those differences will be reflective of the environment in which they inhabit. Given that baby's breath established in these environments approximately 100 years ago (Lamar & Partridge, 2019), we also predict that this should be enough time to see divergence in allele frequencies for genes that are important to these distinct habitats. This will allow us to identify potential targets of local adaptive evolution for future testing.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A perennial iteroparous forb, G. paniculata is native to the Eurasian steppe region and was introduced to North American in the late 1880s [ 25 , 26 ]. Since its introduction, it has spread throughout the western United States and Canada and has established across a diverse array of habitats, including sand dunes, prairies, disturbed roadsides, and sage brush steppes [ 26 , 27 , 28 ]. In Michigan, G. paniculata negatively impacts the coastal dune community by crowding out sensitive species such as Pitcher’s thistle ( Cirsium pitcher ) through direct competition for limited resources, forming monotypic stands in the open dune habitat, preventing the reestablishment of native species, and limiting pollinator visits to native species [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar work assessing the population structure of invasive G. paniculata populations within the mid-western and western United States have found that these invasive populations are distributed among at least two distinct genetic clusters, both of which are present in the Michigan sand dunes [ 28 ]. Our goal for this study was to more extensively sample populations throughout Michigan to gain a better understanding of how these populations are distributed and how they disperse throughout the dune landscape.…”
Section: Introductionmentioning
confidence: 99%